2020
DOI: 10.1038/s41467-020-15907-4
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal gradient in dairy production with the introduction of farming in Atlantic Europe

Abstract: The introduction of farming had far-reaching impacts on health, social structure and demography. Although the spread of domesticated plants and animals has been extensively tracked, it is unclear how these nascent economies developed within different environmental and cultural settings. Using molecular and isotopic analysis of lipids from pottery, here we investigate the foods prepared by the earliest farming communities of the European Atlantic seaboard. Surprisingly, we find an absence of aquatic foods, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 67 publications
(101 reference statements)
1
47
0
4
Order By: Relevance
“…This has important implications for the interpretation of the mode of cooking because it implies that they could theoretically form during a single cooking event rather than from many hours of protracted heating and extensive reuse of a vessel as previously thought. While APAAs are frequently identified in archaeological pottery, they are also notably absent in many archaeological contexts despite large systematic investigation (Whelton et al 2018;Cubas et al 2020). This is surprising given that APAAs are so easily formed from a wide range of products and, even more so, considering that other fatty acid thermal degradation products are frequently encountered in vessels from these contexts (e.g., long-chain ketones C 33 and C 35 ) (Raven et al 1997;Cubas et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This has important implications for the interpretation of the mode of cooking because it implies that they could theoretically form during a single cooking event rather than from many hours of protracted heating and extensive reuse of a vessel as previously thought. While APAAs are frequently identified in archaeological pottery, they are also notably absent in many archaeological contexts despite large systematic investigation (Whelton et al 2018;Cubas et al 2020). This is surprising given that APAAs are so easily formed from a wide range of products and, even more so, considering that other fatty acid thermal degradation products are frequently encountered in vessels from these contexts (e.g., long-chain ketones C 33 and C 35 ) (Raven et al 1997;Cubas et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Possible avenues for studying Neolithic expansion routes from the culinary traditions can be found in the comparison with the first phases of the Neolithic in Northern Greece and on the Atlantic coast of the Iberian Peninsula. These two regions, for which a large amount of data on the contents of pottery is available, also appear to be centred on the exploitation of meat rather than dairy products (Cubas et al, 2020;Whelton et al, 2017).…”
Section: A Distinctive Subsistence Economy?mentioning
confidence: 99%
“…More recently, this type of approach has contributed to deconstructing the overly simplistic model of sedentary European Neolithic societies relying solely on the economy of production. Recent work has shown that regional variation in the degree to which dairy products were processed in early Neolithic pottery (Cubas et al, 2020) and that other products that had no relation to the productive economy, such as fish, were also processed (Craig et al, 2011;Cramp et al, 2019). However, very little work has been carried on early pottery of the North-western Mediterranean.…”
Section: Introductionmentioning
confidence: 99%
“…AverageR is a generalized additive mixed model that employs a thin plate regression spline. Further details on the model can be found in Cubas et al 83 . The local ∆R (10 ± 41 14 C years) was estimated for a point centred at São Luís Island and a radius of 50 km.…”
Section: Statistical Analysis and Bayesian Stable Isotope Mixing Modementioning
confidence: 99%